2015
DOI: 10.1073/pnas.1511570112
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplasts extend stromules independently and in response to internal redox signals

Abstract: A fundamental mystery of plant cell biology is the occurrence of "stromules," stroma-filled tubular extensions from plastids (such as chloroplasts) that are universally observed in plants but whose functions are, in effect, completely unknown. One prevalent hypothesis is that stromules exchange signals or metabolites between plastids and other subcellular compartments, and that stromules are induced during stress. Until now, no signaling mechanisms originating within the plastid have been identified that regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 40 publications
11
153
4
1
Order By: Relevance
“…Considering that a significant proportion of plastidial polyprenols also reside in the chloroplast envelope, it is tempting to speculate that these compounds also influence envelope dynamics, in much the same way as their thylakoid counterparts. Processes that are critically altered by any change in envelope fluidity, such as plastid division (Osteryoung and Nunnari, 2003), metabolite exchange (Mehrshahi et al, 2013), or the sporadic extension and retraction of stroma filled tubules known as stromules (Schattat et al, 2012;Mathur et al, 2013;Brunkard et al, 2015), would conceivably be affected by the abundance of polyprenols. The latter process is particularly relevant in this context as it has long been speculated that stromule formation, for which the mechanism is unknown, requires modulation of plastid envelope membrane architecture (Thomson and Whatley, 1980;Kwok and Hanson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that a significant proportion of plastidial polyprenols also reside in the chloroplast envelope, it is tempting to speculate that these compounds also influence envelope dynamics, in much the same way as their thylakoid counterparts. Processes that are critically altered by any change in envelope fluidity, such as plastid division (Osteryoung and Nunnari, 2003), metabolite exchange (Mehrshahi et al, 2013), or the sporadic extension and retraction of stroma filled tubules known as stromules (Schattat et al, 2012;Mathur et al, 2013;Brunkard et al, 2015), would conceivably be affected by the abundance of polyprenols. The latter process is particularly relevant in this context as it has long been speculated that stromule formation, for which the mechanism is unknown, requires modulation of plastid envelope membrane architecture (Thomson and Whatley, 1980;Kwok and Hanson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, stromule formation was shown to depend on NADPH-dependent TRX reductase C, and silencing its expression doubled the rate of stromule formation. Isolated chloroplasts were able to form stromules, suggesting that stromules intrinsically emerge independent of cytosolic factors (Brunkard et al, 2015), but their emergence might be supported by interaction with microtubules (Kwok and Hanson, 2003). In addition to light and direct changes in redox state, which mimic abiotic stress conditions, stromule formation responds to temperature (Holzinger et al, 2007) and abscisic acid .…”
Section: Reverse Coupling Of Redox Signaling To the Chloroplastmentioning
confidence: 99%
“…Their exact function remains elusive (Natesan et al, 2005). Recently, Brunkard et al (2015) demonstrated that in chloroplasts and leucoplasts, stromules form more frequently in the light than in darkness. Moreover, inhibitors of PET rapidly increase the frequency of stromule formation in chloroplasts, suggesting that redox plays a role in controlling stromule formation.…”
Section: Reverse Coupling Of Redox Signaling To the Chloroplastmentioning
confidence: 99%
“…For instance, it has been suggested that chloroplasts extend stroma filled tubules called stromules in response to internal ROS accumulation following inhibition of the electron transport chain (pETC; Brunkard et al, 2015) and other plastids respond to increased sugar levels in a cell . Similarly, the rapid fission of tubular mitochondria increases their population in a cell in response to high cytosolic sugar content, high ROS levels and light stimuli (Yoshinaga et al, 2005;Yu et al, 2006Yu et al, , 2008Jhun et al, 2013;Jaipargas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%